Foliar silicate fertilization assessment on bean development and its water deficit stress tolerance - Pohlmann, Valeria; Pereira, Bruno Moreira; Knies, Alberto Eduardo; Lazzari, Marcondes; Portalanza, Diego; Ludwig, Fernanda (Scientia Agraria Paranaensis, 2021)
Bean’s productivity is below its productive potential, and among the related factors is the sensitivity to water deficiency. Silicate fertilization may aid to better tolerate this abiotic stress. Therefore, this work aims to evaluate the effects of foliar silicon (Si) doses in the development and tolerance of water deficiency for the bean’s cultivation. The experiment was conducted in a greenhouse, with a completely randomized block design in a 6x2 factorial scheme with four repetitions. Six doses of silicon (0; 0.5; 1.0; 1.5; 2.0; 2.5 kg Si ha-1) with and without water deficiency in flowering were used. The pots with a capacity of 2 L were filled with dystrophic Red Argisol, and they were maintained with automatic irrigation. The leaf temperature (TF) was analyzed daily, and at the end of the cycle, the plants’ height, aerial and root fresh and dry matter, the number of grains per plant, the number of grains per pod, the number of pods per plant, pod length, and grain fresh and dry matter were determined. After water deficit stress, the percentage of absolute integrity and relative water capacity were determined. The water condition reflected differences in plant height, grain dry matter, number of grains per plant, pods per plant, and the foliar temperature. The silicon doses did not influence the development and tolerance to water deficit for the bean culture.